Mission impossible vertical collaboration in Ukraine - Gagalyuk, T.; Hanf, J. (2008)
Food products are increasingly being produced in vertically coordinated networks. While one could argue that supply chain networks and their management are of greater interest in the developed countries, in-depth interviews with agribusiness experts provide evidence that the interest in supply chain management is even greater in the transitional economies. A study of food businesses in Ukraine reveals a number of challenges and barriers supply chain networks face in the transitional economies, the most significant of which are cooperation and coordination issues.
Keywords: Supply chain networks; Chain management